Perlindungan Hukum Bagi Tenaga Kerja Indonesia yang Bekerja di Luar Negeri Ditinjau dari Undang-Undang Nomor 18 Tahun 2017 tentang Perlindungan Pekerja Migran Indonesia - Ana Maria Gadi Djou (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
ABSTRACT: The need to find work causes the demand for jobs to be greater than those available in the country, while other countries need workers. The difficulty of getting a job at home encourages some workers to try their luck abroad. There is no other choice, so they have to work including abroad. The government requires that the Indonesian Migrant Workers must be legal, sent through an official agency that helps them to apply for passports and visas, obtain a health certificate, pay for insurance and other obligations, have language skills and abilities. The low level of education of prospective TKI causes them to face the risk of being easily deceived by other parties. They do not understand the rules and requirements for working abroad. The low number of reports of Indonesian migrant workers experiencing certain cases to the authorities is also based on their concern because they have false identities. This research is a normative legal research, which discusses the legal protection for Indonesian migrant workers before, during, and after working abroad and the protection provided by Law Number 18 of 2017 which replaces Law Number 39 of 2004 concerning Placement and Protection of Indonesian Migrant Workers Abroad. Legal protection for Indonesian migrant workers can be carried out optimally, as long as the parties involved are truly carrying out the agreed laws and regulations. Keywords: Legal Protection, Indonesian Migrant Workers, Law No. 18 of 2017 concerning the Protection of Indonesian Migrant Workers